2000
DOI: 10.1103/physrevb.61.5888
|View full text |Cite
|
Sign up to set email alerts
|

EPR inLa1xCaxMnO3<

Abstract: Recent EPR and susceptibility measurements in La 1Ϫx Ca x MnO 3 support the existence of a bottleneck EPR regime up to 1000 K quantitatively. The EPR linewidth and electrical conductivity follow the same temperature dependence in the range of 250 to 650 K predicted by the small polaron hopping model. This indicates that spin-lattice relaxation in manganates is due to the relaxation of spins of e g Jahn-Teller polarons to the lattice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(115 citation statements)
references
References 14 publications
3
109
3
Order By: Relevance
“…In manganites undergoing a transition from a paramagnetic to ferromagnetic state, the linewidth ∆H(T) in the paramagnetic state is found to increase quasilinearly with increasing T. Different models have been proposed to explain this result such as contribution from spin-phonon interaction 11 , a relaxation bottleneck behavior 20,21 or in terms of a combined effect of DM and CF interactions 12 . The latter model seems to be able to explain most of the CMR EPR linewidth results and can be described in terms of the equation, ∆H(T) = [χ 0 (T) / χ(T)] ∆H(∞) where χ 0 (T) ∝ T -1 is the free ion (Curie) susceptibility, χ(T) is the measured susceptibility and ∆H(∞) is a temperature independent constant attributable to the high temperature limit of the linewidth.…”
Section: Resultsmentioning
confidence: 99%
“…In manganites undergoing a transition from a paramagnetic to ferromagnetic state, the linewidth ∆H(T) in the paramagnetic state is found to increase quasilinearly with increasing T. Different models have been proposed to explain this result such as contribution from spin-phonon interaction 11 , a relaxation bottleneck behavior 20,21 or in terms of a combined effect of DM and CF interactions 12 . The latter model seems to be able to explain most of the CMR EPR linewidth results and can be described in terms of the equation, ∆H(T) = [χ 0 (T) / χ(T)] ∆H(∞) where χ 0 (T) ∝ T -1 is the free ion (Curie) susceptibility, χ(T) is the measured susceptibility and ∆H(∞) is a temperature independent constant attributable to the high temperature limit of the linewidth.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Shengelaya et al showed that the ESR linewidth and electrical conductivity follow the same temperature dependence described by the small polaron hopping model in hole doped ferromagnetic manganites where spin lattice relaxation is mediated by the e g Jahn Teller polarons 47 . This is understandable as the conductivity in mixed valence manganites is determined by the probability of spin conserved e g electron hopping between nearest neighbouring sites while the broadening of the ESR linewidth arises due to the hopping rate of the e g electrons.…”
Section: Figmentioning
confidence: 99%
“…(3). Except in [7] where the authors observed the proportionality between EPR linewidth, ∆H, and conductivity σ(T) ∝ (1/T) exp (-E σ /k B T) taken from [16], we know the only works [8,9] where the EPR linewidth in La 0.7 Ca 0.3 MnO 3 sample was measured in wide temperature range (up to 1000 K). We replotted that data in the scale ln (∆H-T) on 1/T (see insert in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Electron paramagnetic resonance (EPR) has been studied in a variety of lanthanum manganites. Some authors [4,5] attributed the temperature dependence of the EPR linewidth to a spin-phonon interaction (one-phonon relaxation process) and explained it by spin-lattice relaxation of exchange coupled Mn 3+ -Mn 4+ spin system under the condition of a strong relaxation bottleneck [6,7]. Other authors [8 -10] explain the temperature dependence of ESR linewidth by the spin-spin (exchange) interaction.…”
mentioning
confidence: 97%